Effect of Single and Two Level Posterior Instrumented Fusion for L4-5 Degenerative Spondylolisthesis with Adjacent Spinal Stenosis - Pawasuttikul, MD, Chote (Journal of Southeast Asian Orthopaedics, 2022)
Backgrounds: Pedicular screw fixation is the most popular system in instrumented arthrodesis in the lumbar spine. Long- term important complication after lumbar fusion is adjacent segment disease (ASD).The incidence of symptomatic ASD was 5.2-18.5%. Normal progression of degenerative disease and biomechanical alteration played an important role in this disease. However, the cause of ASD is not clear. It has been an attempt to find ways to prevent ASD such as arthroplasty, dynamic fixation and percutaneous fixation. However, it has not been found the effective method. Because adjacent spinal stenosis above single level fusion may increase risk of ASD, therefore we hypothesize that ASD rate will be decrease if we extend spinal fusion to adjacent level. Purpose: To determine the clinical outcome, particularly in the presence ASD, which led to the second operation in patients with degenerative spondylolisthesis of L4-5 and multilevel lumbar stenosis treated with PLF and pedicular screw fixation at L4-5 compare with PLF, Pedicular screw fixation at L4-5 and prophylaxis fixation at L3-4. Methods: 67 patients with degenerative L4 spondylolisthesis (grade I-II) and spinal canal stenosis at L3-5. Group 1,32 patients underwent L4-5 PLF and pedicular screws fixation in 2007-2010, Group 2,35 patients underwent PLF, pedicular screws fixation at L4-5 and prophylaxis fixation at L3-4 in 2011-2013. Based on the obtained data from the patients, pre-operatively, immediately after surgery and at the time of follow-up at 3 months, 6 months, 1 years and then annually afterward including age, sex, BMI, visual analog pain scores (VAS), Oswestry Disability Index (ODI), the occurrence of ASD and the second operation. The data were analyzed by descriptive statistic, Chi-square test and student’s t-test. Results: Surgery patients age average of 55.76 years (range 37-69 years). The mean follow-up period was 65.64 months (range 63-72 months). The recovery rate of VAS score and ODI were not significantly different between the two groups. The lumbar lordosis after operation was decrease in both groups. There were angulation, translation, and decreased disk height at the level above the fusion in both groups but it is not significantly different. Single level fusion group found that grade of listhesis and BMI is a factor affecting ASD (P < 0.05). For the two level fusion groups, the four factors, age, gender, grade of listhesis and BMI did not affect ASD. The occurence of ASD in single level fusion group at L3-4 level in 4 cases (12.5%). Two level fusion group found ASD at L2-3 level in 1 cases (2.85%). The occurrence of ASD between two groups were not significantly different. Conclusion: There is not significantly different in functional outcome between single level or two level fusion with pedicular screws fixation in treatment of patients with degenerative L4 spondylolisthesis and multilevel lumbar stenosis. It cannot be concluded that two level fusion with pedicular screws fixation was the effective way to prevent ASD on cranial segment.